2018
DOI: 10.2134/agronj2017.07.0396
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Nitric Oxide on Photosynthetic Stability and Performance of Silybum marianum under Water Deficit Conditions

Abstract: Core Ideas Milk thistle is a medicinal plant cultivating for production of silymarin and oil.The results our work showed that with the application of SNP photosynthesis, pigments content, and water status were improved in the drought stress condition and as a result significant increases in secondary metabolites production and grain yield was observed.Overall, this study suggest that application of 100 µM SNP and using Sari ecotype can be recommended for maximizing crop yield under drought stress in semiarid e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In the present study, the foliar application of SNP on the sweet violets increased the shoot FW compared to the control. It can be due to the impact of SNP on plant tolerance improvement against stress, increasing the photosynthesis rate and water use efficiency, and increasing photosynthetic availability to sustain vegetative growth and subsequently increase the FW [Zangani et al 2018].…”
Section: Table 3 Means' Comparison For the Interactive Effect Of Wate...mentioning
confidence: 99%
“…In the present study, the foliar application of SNP on the sweet violets increased the shoot FW compared to the control. It can be due to the impact of SNP on plant tolerance improvement against stress, increasing the photosynthesis rate and water use efficiency, and increasing photosynthetic availability to sustain vegetative growth and subsequently increase the FW [Zangani et al 2018].…”
Section: Table 3 Means' Comparison For the Interactive Effect Of Wate...mentioning
confidence: 99%
“…S. marianum contains silymarin, a mixture of flavonoid complexes with a protective component against drugs, including chemotherapy [ 178 ]. Field assays with two genotypes of S. marianum demonstrated that applying the SNP (100 µM) as a NO donor compensates for 40% of the adverse effects caused for drought stress, and all yield components responded significantly to treatment with SNP [ 179 ]. Applying 100 µM SNP also decreased malondialdehyde content and H 2 O 2 in S. marianum plants submitted to water deficit and prevented a silymarin yield reduction but increased taxifolin production, silychristin, silybin, and isosilybin B [ 180 ], compounds that have been associated with the treatment of diseases due to pharmacological properties as hepatoprotective drugs [ 181 , 182 ].…”
Section: Ronss As Biostimulantsmentioning
confidence: 99%
“…Applying 100 µM SNP also decreased malondialdehyde content and H 2 O 2 in S. marianum plants submitted to water deficit and prevented a silymarin yield reduction but increased taxifolin production, silychristin, silybin, and isosilybin B [ 180 ], compounds that have been associated with the treatment of diseases due to pharmacological properties as hepatoprotective drugs [ 181 , 182 ]. Under drought stress applying 100 µM SNP on S. marianum , the leaf photosynthesis rate increased between 80 and 100% compared with the non-treated plants [ 179 ].…”
Section: Ronss As Biostimulantsmentioning
confidence: 99%
“…Several hormones, such as abscisic acid (Kim et al, 2018), methyl jasmonate (Ghasem et al, 2022), salicylic acid (Koramutla et al, 2022), 6‐benzylaminopurine (Zhang et al, 2022a), ethylene (Iqbal et al, 2011), and ethephon (Wang et al, 2016) have been reported to promote grain yield in waterlogged wheat plants. In recent years, several investigations have focused on nitric oxide (NO) as a signalling molecule that plays a crucial role in enhancing waterlogging resistance in plants (Zangani et al, 2018; Zhang et al, 2021a). When wheat is subjected to flooding, its roots synthesize endogenous NO by upregulating the nitric reductase pathway (Aakanksha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%